COVID-19 and Politically Motivated Reasoning. (November 2022) - Maguire, Allegra; Persson, Emil; Västfjäll, Daniel; Tinghög, Gustav
Background: During the COVID-19 pandemic, the world witnessed a partisan segregation of beliefs toward the global health crisis and its management. Politically motivated reasoning, the tendency to interpret information in accordance with individual motives to protect valued beliefs rather than objectively considering the facts, could represent a key process involved in the polarization of attitudes. The objective of this study was to explore politically motivated reasoning when participants assess information regarding COVID-19. Design: We carried out a preregistered online experiment using a diverse sample ( N = 1, 500) from the United States. Both Republicans and Democrats assessed the same COVID-19–related information about the health effects of lockdowns, social distancing, vaccination, hydroxychloroquine, and wearing face masks. Results: At odds with our prestated hypothesis, we found no evidence in line with politically motivated reasoning when interpreting numerical information about COVID-19. Moreover, we found no evidence supporting the idea that numeric ability or cognitive sophistication bolster politically motivated reasoning in the case of COVID-19. Instead, our findings suggest that participants base their assessment on prior beliefs of the matter. Conclusions: Our findings suggest that politically polarized attitudes toward COVID-19 are more likely to be driven by lack of reasoning than politically motivated reasoning—a finding that opens potential avenues for combating political polarization about important health care topics. Highlights: Participants assessed numerical information regarding the effect of different COVID-19 policies. We found no evidence in line with politically motivated reasoning when interpreting numerical information about COVID-19. Participants tend to base their assessment of COVID-19–related facts on prior beliefs of the matter. Politically polarized attitudes toward COVID-19 are more a result of lack of thinking than partisanship. Graphical Abstract This is a visual representation of the abstract.